1999
DOI: 10.1021/jp990866v
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Density of Mo and Acid Sites in Mo-Exchanged H-ZSM5 Catalysts for Nonoxidative Methane Conversion

Abstract: Mo/H-ZSM5 (1.0-6.3 wt % Mo; Mo/Al ) 0.11-0.68) catalysts for CH 4 aromatization were prepared from physical mixtures of MoO 3 and H-ZSM5 (Si/Al ) 14.3). X-ray diffraction and elemental analysis of physical mixtures treated in air indicate that MoO x species migrate onto the external ZSM5 surface at about 623 K. Between 773 and 973 K, MoO x species migrate inside zeolite channels via surface and gas phase transport, exchange at acid sites, and react to form H 2 O. The amount of H 2 O evolved during exchange and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
242
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(266 citation statements)
references
References 26 publications
15
242
0
4
Order By: Relevance
“…Iglesia and co-workers prepared the Mo/HZSM-5 catalysts using solid-state reaction method and studied the location and change of the Mo species during the preparation process in greater detail [47]. They found that the MoO x species migrated onto the external surface first at ca.…”
Section: The Bifunctionality Of the Mo/hzsm-5 Catalystsmentioning
confidence: 99%
“…Iglesia and co-workers prepared the Mo/HZSM-5 catalysts using solid-state reaction method and studied the location and change of the Mo species during the preparation process in greater detail [47]. They found that the MoO x species migrated onto the external surface first at ca.…”
Section: The Bifunctionality Of the Mo/hzsm-5 Catalystsmentioning
confidence: 99%
“…In their recent publications, Iglesia and co-workers studied Mo/HZSM-5 catalysts prepared by using mechanical mixtures of MoO 3 and HZSM-5 via solid exchange reaction [13][14][15][16]. The authors presented evidence that most of the Mo species migrated into the channels and were properly reduced by CH 4 into Mo 2 O x C y .…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that Mo species have a molybdate dimer structure (Scheme 1). 12 We question such a model due to the fact that a dimer, once introduced into the channels and exchanged with the Brønsted acid sites, requires the presence of Si(2Al) sites, which has been proved to be of little possibility to exist in HZSM-5 zeolites. Later, the model was revised and the authors claimed that two Mo atoms will bond to two Si(1Al) sites, 13 which seems to be more reasonable theoretically.…”
Section: Ft-irmentioning
confidence: 99%